Managing and visualizing your BIM data : understand the fundamentals of computer science for data visualization using Autodesk Dynamo, Revit, and Microsoft Power BI /: understand the fundamentals of computer science for data visualization using Autodesk Dynamo, Revit, and Microsoft Power BI. (2021) - Pellegrino, Ernesto; Bottiglieri, Manuel Andre; Crump, Gavin; Pieper, Luisa Cypriano; Touil, Dounia
No abstract available